Uncivil Engagement and Unruly Politics Disruptive Interventions of Urban Youth - Kaulingfreks, Femke; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book explores the significance of riots and public disturbances caused by marginalized youth with a migrant background in France and the Netherlands, and how their demands for recognition, justice and equal opportunities are voiced in uncivil, yet politically meaningful ways.
Keywords: Political science; Democracy; Elections; Europe -- Politics and government; Crime -- Sociological aspects; Political Science and International Relations; European Politics; Democracy; Political Science; Crime and Society; Electoral Politics; Sociology of Family, Youth and Aging; Electronic books